Assessing Diadromous Fish Populations in the Lima River, Northwest Iberian Peninsula - Luís Pereira; Ulisses Azeiteiro; Carlos Antunes (Fishes)
The Lima River in northern Portugal serves as a vital habitat for diadromous fish species, yet it remains one of the least studied aquatic systems in the region. This study investigates the ecology and biology of key diadromous fish populations, including sea lamprey (Petromyzon marinus), shads (Alosa alosa and Alosa fallax), trout (Salmo trutta), and European eel (Anguilla anguilla), during their reproductive migration and riverine periods. A total of 3242 individuals from 15 species were sampled, with native species accounting for 51.1% of the catch. Results revealed significant differences in size and weight of lampreys, with individuals from the Lima River being significantly smaller than those from regional rivers such as the Minho and Mondego. Shad populations showed a high proportion of hybrids (33.8%), suggesting extensive hybridization between A. alosa and A. fallax. Analysis of trout stomach contents revealed a diverse diet dominated by insects (66.9%), crustaceans (6.8%), and fish (6.8%), but also an alarming presence of plastic debris (1.1%), highlighting potential pollution problems. For European eels, this study marks the first record of the invasive swim bladder parasite Anguillicola crassus in the Lima River, with 84.8% of eels sampled showing moderate to severe swim bladder damage. These findings contribute to a deeper understanding of diadromous fish ecology and emphasize the importance of conservation efforts in estuarine systems worldwide.